Working-Through Christianity: Lacan and Atheism - Johnston, Adrian (Filozofski vestnik, 2019)
Whereas Sigmund Freud’s rapport with religious content seems unambiguously antagonistic, Jacques Lacan’s relationship with religion generally and Christianity particularly appears to some to have a different, more ambivalent character. This apparent ambivalence has led to readings of Lacan according to which he is either a principled agnostic on (anti-)philosophical grounds or even an especially subtle (Christian) theological thinker. Herein, I argue against both of these types of readings by exhaustively establishing Lacan’s atheist credentials. In so doing, I seek, first, to elucidate the distinctive Lacanian conception of the essential features of true atheism and, second, to distinguish atheism à la Lacan from other varieties of irreligiosity. Moreover, I revisit the later years of Lacan’s teaching with an eye to asking questions about belief and disbelief pushing off from crucial points Lacan makes primarily during this period: Is atheism an indispensable aspect of the analytic experience? Can analysis produce subjects fully divested of any trace of theistic commitments? Is it possible and/or desirable for persons to abandon entirely everything associated with religiosity? What might the consequences of such abandonment be for subjects’ libidinal, desiring lives? If certain theistic dimensions are inescapable horizons for speaking subjectivity, is there any prospect for the invention, perhaps aided by psychoanalysis, of historically unprecedented forms of what religion has covered throughout history hitherto?